Six new species and a new record of Curcuma L. (Zingiberaceae) from Thailand - Surapon Saensouk; Thawatphong Boonma; Piyaporn Saensouik (Biodiversitas Journal of Biological Diversity, 2021)
Abstract. Saensouk S, Boonma T, Saensouk P. 2021. Six new species and a new record of Curcuma L. (Zingiberaceae) from Thailand. Biodiversitas 22: 1658-1685. All six new species and a new record of Curcumawere described with detailed illustrations, photographs, summaries for their distribution, ecology, IUCN conservation status, and followed by a new record and key to 63 species of Curcuma revised and present in Thailand. The study surveyed six new species and a new record of Curcuma to collect, describe, measure, and illustrate the living and spirit specimens under a stereoscopic microscope. Plant materials and photographs were collected in the field from 2018 to 2019. The results of the study described six new species, including Curcuma chantaranothaii Boonma & Saensouk sp. nov., C. charanii Boonma & Saensouk sp. nov., C. rangsimae Boonma & Saensouk sp. nov., C. phrayawan Boonma & Saensouk sp. nov., C. puangpeniae Boonma & Saensouk sp. nov., C. purpurata Boonma & Saensouk sp. nov., and a first new record of C. peramoena. All six new species were recognized to be endemic to Thailand.